THEO-PROPHETIC JURISPRUDENCE: TRACING THE GENEALOGY OF THE ISLAMIC LAW’S FORMATION AND GROWTH IN RASULULLAH ERA - Kholish, Moh Anas; Galib, Andi Muhammad (Universitas Brawijaya, 2023)
This paper concisely and analytically presents the history of tasyri', or the formation of Islamic law in the Prophet's era. By using the term